Online Community, Analysis of Marginal School Communities to Increase Self Potential - Airlangga PH, Ahmad Rahmatullah; Fitri, Ramadhani Ayu (Journal of Sumatera Sociological Indicators, 2024)
Technological changes in this day and age mean that people in all parts of the world can communicate with each other, even over long distances. In Indonesia itself, there is a lot of use of online platforms in cyberspace. One of them is by creating an Online Community which allows a group of people to gather with the same goal to solve or discuss problems that are happening around them. Marginal school communities become online community forums for those interested in being part of volunteering who live in Yogyakarta. The volunteer action in question is carrying out various program plans which are considered to help improve personal quality and create personal potential for street children and marginalized children who do not receive the rights they should have. So, it can be seen that the Marginal School Community recruits online through their personal Instagram account called (@sekolah_marjinal). This Marginal School Community carries out various programs that support street children, such as teaching and learning programs, posyandu programs and community health centers and identity advocacy programs. The method used in this research to collect data is literature study, which involves searching or reading data from journals, books, related websites and scientific articles.